TNFR2 Expression on CD25hiFOXP3+ T Cells Induced upon TCR Stimulation of CD4 T Cells Identifies Maximal Cytokine-Producing Effectors - Govindaraj, Chindu; Scalzo-Inguanti, Karen; Scholzen, Anja; Li, Shuo; Plebanski, Magdalena (Frontiers in Immunology, 2013)
In this study, we show that CD25hiTNFR2+ cells can be rapidly generated in vitro from circulating CD4 lymphocytes by polyclonal stimuli anti-CD3 in the presence of anti-CD28. The in vitro induced CD25hiTNFR2+ T cells express a conventional regulatory T cells phenotype FOXP3+CTLA4+CD127lo/−, but produce effector and immunoregulatory cytokines including IL-2, IL-10, and IFN-g. These induced CD25hiTNFR2+ T cells do not suppress target cell proliferation, but enhance it instead. Thus the CD25hiTNFR2+ phenotype induced rapidly following CD3/28 cross linking of CD4 T cells identifies cells with maximal proliferative and effector cytokine-producing capability. The in vivo counterpart of this cell population may play an important role in immune response initiation.